Birds of Alas Purwo National Park, East Java - M J Grantham (KUKILA, 2000)
This paper details some of the more important and interesting records from Alas Purwo National Park in East Java. Most of these come from the author's work in the Park from May 1997 until September 1999, though records are included from many other sources. Details are given of the status of all of the species that are classed as threatened or near-threatened by Collar et al. (1994), along with those that are attitudinally or distributionally unexpected. A full systematic list of the species recorded in and around the Park is included, some 227 to date (with an additional 11 'possible' species).